Studi Historis Kebijakan Luar Negeri Sultan Abdul Hamid II di Daulah ‘Utsmaniyah (1876-1909 M) - Rizka Kusuma Rahmawati (UIN Sumatera Utara Medan, 2017)
Sultan Abdul Hamid II has led Daulah 'Utsmaniyah for 33 years. In the early days he ruled, daulah conditions are experiencing many problems. Great state debts, great westernization efforts to changing political conditions from before. This political situation that influenced the Sultan Abdul Hamid II in determining the foreign policy of Daulah 'Ottoman. In the days of war with the Ottoman state outside the Ottomans, they tried to seize the territory of Sultan Abdul Hamid II, agreements are also established between several countries. Diplomacy that took place between other countries is interesting to see the figure of Abdul Hamid II in running its performance in Daulah 'Ottoman.